Experimental investigation on effects of fuel injection and intake parameters on combustion and performance of a turbocharged diesel engine at different altitudes - Wan, Mingding; Huang, Fenlian; Shen, Lizhong; Lei, Jilin (Frontiers in Energy Research, 2023)
Matching characteristics between fuel injection and intake control parameters significantly affect overall performances in diesel engine at variable altitudes. Prior to optimizing the control parameters of diesel engines operating at high altitudes areas, there is a necessity to identify the influence law of fuel injection and intake parameters on engine performance. This study focused on the effects of main injection timing (MIT), fuel injection pressure (FIP), EGR rate, and variable nozzle turbocharger (VNT) opening on the combustion, performances and NOx and smoke emissions in a turbocharged diesel engine at different altitudes (2000, 1000, and 0 m). Strategies for optimization of engine performance and the coupling relationship between these parameters were analyzed. The results showed that as the altitude increased from 0 m to 2000 m, the engine torque dropped by 2.9%, the BSFC increased by 2.6%, the NOx emissions reduced by 11.8%, and the opacity smoke increased by 26.2%. The effects of MIT, FIP, EGR rate and VNT opening on engine performances were more significant at high altitudes. As the MIT was advanced at 2000 m altitude, the engine torque increased by 5.6%, the BSFC reduced by 5.9%, the opacity smoke decreased by 55%, while the NOx emissions increased by 54%%. Advance the injection timing properly can overcome the altitude effect on engine power. With the FIP increased from 105 to 130 MPa at 2000 m, the torque reduced by 1.7%, BSFC increased by 1.6%, the opacity smoke dropped by 44.5%, and the NOx emissions increased by 17.5%. When the EGR rate increases by 5%, the NOx emission reduces by 16.4%,17.9 and 21.9 respectively at 0, 1000 and 2000 m altitude. The EGR rate should be properly reduced to obtain the recovery of engine power at plateau. As the VNT opening decreased from 40% to 20%, the NOx emission increase by 9.4% and 9.9% at 0 m and 1000 m respectively, and it reduces by 3.9% at 2000 m, while the opacity smoke reduces by 38.9% at different altitudes. The multi-objective collaborative optimization technique should be applied to optimize these parameters to improve engine efficiency and emissions at high altitudes.